Investigating the activation of passive metals by a combined in-situ AFM and Raman spectroscopy system: a focus on titanium - L. Casanova; M. Menegazzo; F. Goto; M. Pedeferri; L. Duò; M. Ormellese; G. Bussetti (Scientific Reports, 2023)
Abstract Understanding the main steps involved in the activation of passive metals is an extremely important subject in the mechanical and energy industry and generally in surface science. The titanium-H2SO4 system is particularly useful for this purpose, as the metal can either passivate or corrode depending on potential. Although several studies tried to hypothesise the surface state of the electrode, there is no general consensus about the surface state of Ti in the active–passive transition region. Here by combining in-situ atomic force microscopy (AFM) and Raman spectroscopy, operating in an electrochemical cell, we show that the cathodic electrification of Ti electrodes causes the dissolution of the upper TiO2 portion of the passive film leaving the electrode covered by only a thin layer of titanium monoxide. Fast anodic reactions involved the acidification of the solution and accumulation of sulphur containing anions. This produces a local increase of the solution turbidity, allowing to distinguish favourable regions for the precipitation of TiOSO4·2H2O. These results give a clear answer to the long-stated question of the physical origin behind the formation of negative polarization resistances, sometimes occurring in corroding systems, and a rationale about the proton-induced degradation of passive surfaces in presence of sulphur containing species.